Common Haplotypes within the Chromosome 1q31.3 Region Determine Systemic Concentrations of the Entire Complement Factor H Protein Family - Bert R.J. Veuskens; Mara van Rossum; Emi Cattenstart; Mieke C. Brouwer; Gerard van Mierlo; Judy Geissler; Karin van Leeuwen; Jin Liu; Robert A. Anstadt; Burt T. Richards; Gregory S. Hageman; Taco W. Kuijpers; et al. (Journal of Innate Immunity)
Introduction: The alternative pathway of complement activation is consistently active, keeping the complement system primed for immediate response. This constant “tick-over” mechanism is regulated by the factor H (FH) protein family, which encompasses seven highly related proteins: FH, FHL-1, and five FH-related (FHR-1 to -5) proteins. The current model is that the FHRs compete with FH and FHL-1 to fine-tune their activities. Genetic studies of this complex locus have revealed distinct haplotypes associating with a wide array of human diseases, underscoring its significant role in complement regulation. Nevertheless, a comprehensive analysis of systemic concentrations of all FH protein family members, accounting for known genetic variability within the population, is still lacking. Methods: Systemic levels of each member of the FH protein family were quantified with the use of recently developed target specific ELISAs. Next, a genetic analysis focused on the chromosome 1q31.3 region was performed using next generation sequencing and multiplex ligase probe-dependent amplification. Results: We report systemic protein levels of each member of the FH protein family found in vivo and demonstrate common haplotypes within the CFH locus give rise to classifiable protein expression patterns, establishing distinct ratios between FH, FHL-1, and the FHRs. Conclusions: The established reference intervals and identified genetic effects provide a benchmark for further research and emphasize the importance of including all family members when studying their role in both health and disease.